Social influences on Moroccan and Pakistani immigrant women’s access and use of cervical cancer screening in Catalonia, Spain: a social network analysis - Harling, Guy (BioMed Central, 2025)
Background: Participation in cervical cancer (CC) screening programs is lower among immigrants compared to native women in many Western countries, in substantial due to lower knowledge and culturally influenced attitudes regarding self-care and prevention. Education and information programs alone have limited impact on individuals’ attitudes and behaviours, but may be bolstered by social influence methods such as peer support. Methods: In this study, we combined self-reported quantitative structural social network data with qualitative narratives and graphs to describe the social context of 12 Moroccan and 10 Pakistani immigrant women living in Catalonia, Spain. We used a survey protocol and semi-structured interviews to explore how women’s contacts influence their CC screening behaviours. Results: We identified strong gender and ethnic homophily in these women’s social networks. Despite maintaining frequent remote contact with their family ties, their immigrant peers were more influential in providing health information and advice. Furthermore, the women’s husbands played two conflicting roles as health promoters and as a barrier to the use of health prevention services. Conclusion: Our findings highlight the need to incorporate tailored social influence approaches in the design of behaviour change interventions. In this case, the use of peer-based programs to increase CC screening uptake among these two immigrant communities.
Keywords: Behaviour change; Cervical cancer; Health inequities; Migrant health; Screening; Social influence; Social network analysis; SDG-3: Good health and well-being